2021
DOI: 10.1177/0022002721995547
|View full text |Cite
|
Sign up to set email alerts
|

The Tactical Use of Civil Resistance by Rebel Groups: Evidence from India’s Maoist Insurgency

Abstract: Research on rebel behavior during conflicts has traditionally focused on the use of violent tactics. However, evidence from several intrastate wars suggests that armed groups also occasionally employ general strikes—a method of civil resistance that has typically been associated with nonviolent groups. But when do rebels resort to general strikes? I argue that these tactics have a particular function which can offset potential risks for rebels after they have suffered losses in previous battles: Through genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Existing quantitative research on nonviolent campaigns has often treated such campaigns as monolithic. There has been an increase in scholarship on violent flanks, as well as tactical diversity within largely nonviolent campaigns, with recent work showing that many actors use both violence and nonviolence (Cunningham, Dahl & Frugé, 2017; Hallward, Masullo & Mouly, 2017; Belgioioso, 2019; Breslawski, 2021; Krtsch, 2021; Gleditsch & Abbs, 2022 ). While recent scholarship has produced datasets focused more on organizations as the primary unit of analysis (Butcher et al, 2022; Pinckney, Butcher & Braithwaite, 2022), most existing quantitative scholarship treats events or campaigns as the primary units of analysis, neglecting the complexities of diversity within coalitions.…”
Section: Sources Of Fragmentationmentioning
confidence: 99%
“…Existing quantitative research on nonviolent campaigns has often treated such campaigns as monolithic. There has been an increase in scholarship on violent flanks, as well as tactical diversity within largely nonviolent campaigns, with recent work showing that many actors use both violence and nonviolence (Cunningham, Dahl & Frugé, 2017; Hallward, Masullo & Mouly, 2017; Belgioioso, 2019; Breslawski, 2021; Krtsch, 2021; Gleditsch & Abbs, 2022 ). While recent scholarship has produced datasets focused more on organizations as the primary unit of analysis (Butcher et al, 2022; Pinckney, Butcher & Braithwaite, 2022), most existing quantitative scholarship treats events or campaigns as the primary units of analysis, neglecting the complexities of diversity within coalitions.…”
Section: Sources Of Fragmentationmentioning
confidence: 99%
“…Literature [7] re-examined the importance of information exchange in preventing local insurgency and conflict in countries where government control is not strong enough, and based on the social experiment of information campaigns in Afghanistan, it was found that smooth information disclosure effectively promoted civil cooperation. Literature [8] in the analysis of the behavior of the Maoist armed conflict in the eastern region of India suggests that in addition to violent tactics, civil resistance methods can be used to deal with rebel acts of governance. The article highlights the strategic role played by the people at large in governing local conflicts.…”
Section: Relevant Studiesmentioning
confidence: 99%
“…Jiangkun Qin and Xia Hong. Applied Mathematics and Nonlinear Sciences, 9(1) (2024)[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] …”
mentioning
confidence: 99%
“…Second, I provide new insights on the prevalence and characteristics of wartime civilian protest. Although several subnational datasets capture wartime civilian protest—in Colombia (Arjona 2015; Kaplan 2017; Masullo 2021), India (Krtsch 2021), and Syria (Svensson et al 2022)—there is a lack of event data that capture protests to all different ends and provide sufficient detail to disaggregate protest types 1 . Arjona, Kaplan, and Masullo all limit their focus to civilian protests against violence and war, Krtsch (2021) records only rebel-organized strikes, and Svensson et al (2022) document only protests against jihadist insurgents.…”
Section: Introductionmentioning
confidence: 99%
“…Although several subnational datasets capture wartime civilian protest—in Colombia (Arjona 2015; Kaplan 2017; Masullo 2021), India (Krtsch 2021), and Syria (Svensson et al 2022)—there is a lack of event data that capture protests to all different ends and provide sufficient detail to disaggregate protest types 1 . Arjona, Kaplan, and Masullo all limit their focus to civilian protests against violence and war, Krtsch (2021) records only rebel-organized strikes, and Svensson et al (2022) document only protests against jihadist insurgents. My database of civilian protest in Côte d’Ivoire thus provides a first glimpse of the prevalence, characteristics, and agents of civilian protest, and allows for a comparison across protest types.…”
Section: Introductionmentioning
confidence: 99%